Swinhopeptolides A and B: Cyclic Depsipeptides from the Sponge Theonella swinhoei that Inhibit Ras/Raf Interaction - Kim, Chang-Kwon (J Nat Prod, 2020)
Two new cyclic depsipeptides named swinhopeptolides A (1) and B (2), have been isolated from the marine sponge Theonella swinhoei cf. verrucosa, collected from Papua New Guinea. They each contain 11 diverse amino acid resudues and 13-carbon polyketide moieties attached at the N-terminus. Compounds 1 and 2 each exist as two conformers in DMSO-d(6) due to cis/trans isomerism of the proline residue, and their structures were successfully assigned by extensive NMR analyses complemented by chemical degradation and derivatization studies. Swinhopeptolide B (2) contains a previously undescribed 2,6,8-trimethyldeca-(2E,4E,6E)-trienoic acid moiety N-linked to a terminal serine residue. Swinhopeptolides A (1) and B (2) showed significant inhibition of the Ras/Raf signaling pathway with IC(50) values of 5.8 and 8.5 μM, respectively.